Climate Change and the Impact of Greenhouse Gasses: CO2 and NO, Friends and Foes of Plant Oxidative Stress - Cassia, Raúl; Nocioni, Macarena; Correa-Aragunde, Natalia; Lamattina, Lorenzo (Frontiers in Plant Science, 2018)
Here, we review information on how plants face redox imbalance caused by climate change, and focus on the role of nitric oxide (NO) in this response. Life on Earth is possible thanks to greenhouse effect. Without it, temperature on Earth's surface would be around −19°C, instead of the current average of 14°C. Greenhouse effect is produced by greenhouse gases (GHG) like water vapor, carbon dioxide (CO2), methane (CH4), nitrous oxides (NxO) and ozone (O3). GHG have natural and anthropogenic origin. However, increasing GHG provokes extreme climate changes such as floods, droughts and heat, which induce reactive oxygen species (ROS) and oxidative stress in plants. The main sources of ROS in stress conditions are: augmented photorespiration, NADPH oxidase (NOX) activity, β-oxidation of fatty acids and disorders in the electron transport chains of mitochondria and chloroplasts. Plants have developed an antioxidant machinery that includes the activity of ROS detoxifying enzymes [e.g. superoxide dismutase (SOD), ascorbate peroxidase (APX), catalase (CAT), glutathione peroxidase (GPX), and peroxiredoxin (PRX)], as well as antioxidant molecules such as ascorbic acid (ASC) and glutathione (GSH) that are present in almost all subcellular compartments. CO2 and NO help to maintain the redox equilibrium. Higher CO2 concentrations increase the photosynthesis through the CO2-unsaturated Rubisco activity. But Rubisco photorespiration and NOX activities could also augment ROS production. NO regulate the ROS concentration preserving balance among ROS, GSH, GSNO and ASC. When ROS are in huge concentration, NO induces transcription and activity of SOD, APX, and CAT. However, when ROS are necessary (e.g. for pathogen resistance), NO may inhibit APX, CAT and NOX activity by the S-nitrosylation of cysteine residues, favoring cell death. NO also regulates GSH concentration in several ways. NO may react with GSH to form GSNO, the NO cell reservoir and main source of S-nitrosylation. GSNO could be decomposed by the GSNO reductase (GSNOR) to GSSG which, in turn, is reduced to GSH by glutathione reductase (GR). GSNOR may be also inhibited by S-nitrosylation and GR activated by NO. In conclusion, NO plays a central role in the tolerance of plants to climate change.